2019
DOI: 10.1007/s00146-019-00879-x
|View full text |Cite
|
Sign up to set email alerts
|

The future of war: could lethal autonomous weapons make conflict more ethical?

Abstract: Lethal Autonomous Weapons (LAWs) are robotic weapon systems, primarily of value to the military, that could engage in offensive or defensive actions without human intervention. This paper assesses and engages the current arguments for and against the use of LAWs through the lens of achieving more ethical warfare. Specific interest is given particularly to ethical LAWs, which are artificially intelligent weapon systems that make decisions within the bounds of their ethics-based code. To ensure that a wide, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
3
Order By: Relevance
“…It will become particularly constructive to consider the transparency of human actions and motivations in this respect [1,66]. This can be extended similarly to other AI systems such as autonomous weapons systems and the ability for those systems to understand non-verbal commands given by friendly combatants, or even non-friendly ones, such as in cases where enemy combatants or civilians surrender [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…It will become particularly constructive to consider the transparency of human actions and motivations in this respect [1,66]. This can be extended similarly to other AI systems such as autonomous weapons systems and the ability for those systems to understand non-verbal commands given by friendly combatants, or even non-friendly ones, such as in cases where enemy combatants or civilians surrender [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…97 Considered in the military context, these insights question the overly optimistic view on AI becoming the ultimate solution for awareness and precision issues. For example, it was suggested that AI could make war 'more ethical' 98 if 'drones could be taught not to shoot at "protected symbols" such as the red cross sign, or not to shoot at children, by being trained not to target people below a certain height' . 99 Quite apart from the technological feasibility of using AI reliably in combat, such understandings do not accommodate the established research on AI vulnerability.…”
Section: Vision Under Attack: Adversarial Examplesmentioning
confidence: 99%
“…As the object of the international law regulation of the MPP circulation should be considered a system of economic relations of a public-law nature between the subjects of international law in the sphere of the MPP circulation. Economic relations in the area of the MPP circulation include trade relations in which a state satisfies its needs for weapons and military equipment by purchasing them from another state 17 .…”
Section: International Law Aspects Of International Circulation Of Military Purpose Products (Mpp)mentioning
confidence: 99%